2022
DOI: 10.1515/cclm-2021-1012
|View full text |Cite
|
Sign up to set email alerts
|

S100B in cardiac surgery brain monitoring: friend or foe?

Abstract: Recent advances in perioperative management of adult and pediatric patients requiring open heart surgery (OHS) and cardiopulmonary bypass (CPB) for cardiac and/or congenital heart diseases repair allowed a significant reduction in the mortality rate. Conversely morbidity rate pattern has a flat trend. Perioperative period is crucial since OHS and CPB are widely accepted as a deliberate hypoxic-ischemic reperfusion damage representing the cost to pay at a time when standard of care monitoring procedures can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 141 publications
0
11
0
Order By: Relevance
“…This phenomenon is exaggerated by the use of cardiotomy suction and autotransfusion (22). Given the relatively short half-life of S100B, it has been suggested that measurements 24-48 hours after surgery would be less in uenced by contamination from the surgical site (22). Therefore, we believe that the results at T1 were driven by contamination rather than cerebral injury.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…This phenomenon is exaggerated by the use of cardiotomy suction and autotransfusion (22). Given the relatively short half-life of S100B, it has been suggested that measurements 24-48 hours after surgery would be less in uenced by contamination from the surgical site (22). Therefore, we believe that the results at T1 were driven by contamination rather than cerebral injury.…”
Section: Discussionmentioning
confidence: 90%
“…S100B has a short half-life of about 30-60 min and is mainly eliminated by the kidneys (22). The physiological role of S100B is not yet fully understood but depending on its concentration, it can act as a neurotrophic or a neurotoxic factor with high tissue concentrations driving the latter (22). Until recent years, S100B has been believed to passively leak from damaged cells and enter the circulation due to the compromised integrity of the blood brain barrier.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations